2014
DOI: 10.4300/jgme-06-01-37.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Resident Learning Preferences Within an Internal Medicine Noon Conference Lecture Series: A Qualitative Study

Abstract: Background The lecture remains the most common approach for didactic offerings in residency programs despite conflicting evidence about the effectiveness of this format. Objective The purpose of this study was to explore the perspectives of internal medicine residents toward conferences held in the lecture format. Methods The investigators invited internal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Active participation in educational sessions has been reported by residents to increase attention and engagement learning 17. The format of active learning sessions is important.…”
Section: Resultsmentioning
confidence: 99%
“…Active participation in educational sessions has been reported by residents to increase attention and engagement learning 17. The format of active learning sessions is important.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the adherence to the template might have been adversely affected by the lack of formally required instructions about being compliant with the template. It is well-known that residents also appreciate a safe learning environment, which we were not able to specifically quantify [16]. This study also did not test how the sessions affected learning retention, such as with a before-and-after written test, or a change in resident anesthesia clinical practice.…”
Section: Discussionmentioning
confidence: 95%
“…13 Several studies suggested that case-based training is highly effective when fellows are actively engaged. 6,14 For example, case-based training was effective in teaching arrhythmia management during residency. 15 However, the risk with relying exclusively on a case-based approach is that some topics may be neglected when the case load is unbalanced.…”
Section: Case-based Learningmentioning
confidence: 99%
“…[3][4][5] Training is likely to be most effective if the programme both adheres to the fellows' preferences and utilises evidence-based teaching strategies. 6 Adult CHD is a nascent subspecialty which is rapidly expanding in response to increasing numbers of adults living with moderate or complex CHD, typically after having undergone paediatric surgical interventions. [7][8][9] Specialised adult CHD clinical programmes have been developed across the globe, and many now also offer dedicated adult CHD subspecialty fellowships.…”
mentioning
confidence: 99%